2021
DOI: 10.1093/jbcr/irab106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Burn Admissions at a Major Metropolitan Burn Center

Abstract: The impact of the COVID-19 pandemic on admission patterns and outcomes at a burn center is still largely unknown. The aim for this study was to determine how the COVID-19 pandemic affected the epidemiology of burn admissions at a major metropolitan burn center. This retrospective cohort study examined how the COVID-19 pandemic impacted burn volumes and time to presentation. All burn admissions were included from January 20 th – August 31 st for the years 2020, 2019, & 2018. The COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…This is in contrast to the results of other studies that addressed this topic, which noted a decrease in total admissions ranging from 7% to 49% during the pandemic [ 5 9 ]; however, a study conducted by Codner et al. reported relatively stable inpatient admissions over the course of the pandemic, as well as an increase in burns that required surgical treatment during shelter-in-place orders [ 4 ]. Two other studies showed that there was a significant increase in ethyl alcohol burns during the COVID-19 pandemic, due to increased use of disinfectants [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 82%
“…This is in contrast to the results of other studies that addressed this topic, which noted a decrease in total admissions ranging from 7% to 49% during the pandemic [ 5 9 ]; however, a study conducted by Codner et al. reported relatively stable inpatient admissions over the course of the pandemic, as well as an increase in burns that required surgical treatment during shelter-in-place orders [ 4 ]. Two other studies showed that there was a significant increase in ethyl alcohol burns during the COVID-19 pandemic, due to increased use of disinfectants [ 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Similar studies were published by other burn centres from economically developed countries, such as the UK, the US, Canada, and Japan [ 5 , 10 , 11 , 12 , 13 ]. D'Asta et al reported a decrease in adult burn patients by 60% during the lockdown, although the number of paediatric burn cases increased by 8% at the same time [11] .…”
Section: Discussionsupporting
confidence: 78%
“…Our specialised centre does not treat paediatric burn patients, and thus this study does not give insight regarding the incidence of paediatric burn patients. A slight decrease of admitted burn patients by 5.8% was reported by Codner et al [12] . Further, a regional burn centre located in the UK reported a 30% decrease in adult burns during the COVID-19 pandemic [13] .…”
Section: Discussionmentioning
confidence: 72%
“…Although some burn units have reported their measures [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], there are no data on the impact of these with regard to treatment outcomes. Most of the data published in the literature thus far refer to epidemiological and demographic data in addition to injury and treatment characteristics of burn patients [ 8 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%